Fostering research literate science teachers: Science teacher educators’ views on research-based teacher education - Siv Gundrosen Aalbergsjø; Ellen Karoline Henriksen; Gunilla Eklund (Nordina: Nordic Studies in Science Education, 2023)
Science teacher educators (STEs) are key actors for implementing research-based science teacher education (RBSTE). Based on group interviews with 29 STEs from seven different teacher education (TE) institutions in Norway, this study reports how STEs view RBSTE. The STEs did not express a comprehensive understanding of the term RBSTE; however, their descriptions of the aims of science TE were in line with educating research literate teachers - critical and reflective teachers who can develop their practice based on research. They regarded their own competence as decisive for RBSTE and described modelling research-based practices in science education as a way of teaching science and science education simultaneously. However, the STEs described tension between prioritising natural science and science education research. We conclude that STEs’ goals and practices are in line with the aims for RBSTE, but a stronger common understanding of what RBSTE entails is needed to further strengthen science TE.